Crush depth - Andry, David; Daniel, Tim (Comic book creator) (Mad Cave Studios, LLC, 2025)
"A deep sea submarine horror adventure series that deals with the world-shattering effects of environmental cataclysm and the struggle for power between two brothers. Two brothers locked in a sibling rivalry wrestle for command of a massive nuclear submarine, The Absolution, in a near-future irrevocably altered by climate change. Chief Science Officer Liana Pearson finds herself not only caught between the Wilder brothers, but drowning in her fear of the surface world. When something alien infiltrates The Absolution and upends the balance of power, Liana is left with only two deadly options--reaching the toxic surface world or steering the sub into the unforgiving abyss and crush depth--Breathe Deep!"